"You Don't See Them on the Streets of Your Town": Challenges and Strategies for Serving Unstably Housed Veterans in Rural Areas. Issue 3 (3rd May 2020) - Byrne, Thomas; Cusack, Meagan; True, Gala; Montgomery, Ann Elizabeth; Smith, Megan
ABSTRACT: Research on policy and programmatic responses to homelessness has focused largely on urban areas, with comparatively little attention paid to the rural context. We conducted qualitative interviews with a nationwide sample of rural-serving agencies receiving grants through the U.S. Department of Veterans Affairs' Supportive Services for Veteran Families program to better understand the housing needs, available services, needed resources, and challenges in serving homeless and unstably housed veterans in rural areas. Respondents discussed key challenges—identifying unstably housed veterans, providing services within the rural resource context, and leveraging effective collaboration—and strategies to address these challenges. Unmet needs identified included emergency and subsidized long-term housing options, transportation resources, flexible financial resources, and additional funding to support the intensive work required in rural areas. Our findings identify promising programmatic innovations and highlight the need for policy remedies that are responsive to the unique challenges of addressing homelessness and housing instability in rural areas.